Diversity Soil Surface Insects in Baby Kailane (Brassica oleraceae Var. Alboglabra) Used Pitfall Trap Method - Elly Roosma Ria; Agus Surya Mulya; Lia Lisnawati; Zahra Nur Safa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This research aims to study various types of ground surface insects on kailan cultivated land using pitfall trap method and identify diversity of ground surface insects on kailan cultivated land using pitfall trap method. Research was carried out in experimental garden of Cikole village, West Bandung Regency, which is at an altitude of 1100 m above sea level (asl) with Latosol soil order and experiment was carried out from July to August 2024. Method used in this research is pitfall trap method. Traps were installed on kailan plantations at a distance of 5 m and 10 points were determined, namely 5 sheltered trap points and 5 exposed trap points. Results of research show that soil surface insect diversity index on kailan cultivation land is relatively low because H < 1 and soil surface insect dominance index is medium to high, where dominance index ranges from 0.63 to 0.95, which means that 0.75 < C < 1 (High) and 0.5 < C < 0.75 (medium) on baby kailan cultivation land using pitfall trap method and insect diversity index on kailan plant cultivation land contains 35 families belonging to 10 orders and insect dominance index is found in order Collembola with family Entomobryidae.